Insights into metal depuration in different tissues of the burrowing crab Neohelice granulata (Dana, 1852) - Truchet, Daniela María (2023)
In this article, we address the limited understanding of the recovery abilities of estuarine organisms following exposure to metals and the lack of research on the mechanisms involved in metal sequestration and detoxification. Specifically, our focus is on the burrowing crab, Neohelice granulata, found in the Bahía Blanca estuary. The objectives of this study were to a) evaluate the metal content in various tissues of N. granulata before and after the depuration process, b) identify metal-rich granules (MRG) in the crabs' hepatopancreas and c) examine the relationship between metal loads and the induction/activity or reversibility of biochemical biomarkers. Following the depuration treatment, a noticeable decrease in metals was observed in the soft tissues compared to the hepatopancreas and the shell. Specifically, the depuration process effectively eliminated Mn and Fe in the form of MRG, but no significant differences were found for other metals, suggesting that MRG might not be the primary detoxification mechanism. Glutathione reductase (GR) and metallothionein (MT) levels significantly decreased after depuration. However, it is worth noting that the duration of the depuration period might not have been sufficient to fully counteract the oxidative stress and damage caused by field exposure.